Verbs, Denoting Insincere Behavior of a Man in Amirkhan Eniki’s Works and Semantic Correspondences in the Translation of them into Russian - Ruzilya Rashitovna SALAKHOVA; Firuza Ramzelovna SIBGAEVA (Astra Salvensis, 2019)
The article is devoted to the study of the lexical-semantic group of verbs of behavior, where the following principles of behavior are implicitly presented: in relations with other people it is necessary to hold naturally, be sincere in words and deeds, be honest, highly moral. Rules in the semantics of verbs ensure the harmonious existence of man in society. The globalization processes of our time, the need to build effective relationships with people, including representatives of other nations, make the topic of this study topical. Therefore, studies, in which language is seen as the bearer of the cultural "behavioral" code of ethnos, remain in demand in modern linguistics. In this study, Tatar and Russian verbs of behavior are compared in terms of their lexical compatibility. The materials for the study were the works of A. Eniki. A. Eniki classic of Tatar literature, one of the most revered authors of the twentieth century. His works are of great interest for linguists studying various aspects of the development of the Tatar literary language. Verbs of behavior in A. Eniki's works are also important for studying this lexico-semantic group.